The applicability and efficacy of Micro-Video Psychological Training Camp in groups with mild to moderate symptoms of depression and anxiety: A prospective and randomized controlled trial protocol - Zhao, Wenqing; Chen, Shuangyi; Hu, Jun; Zhou, Qing; Tao, Jing; Gao, Rui; Zhang, Jie; Su, Shanshan; Wang, Yuan; Su, Yousong; Peng, Yihua; Wu, Yanru; et al. (Frontiers in Psychiatry, 2023)
Background: Mental health is a global issue requiring global attention. Depression and anxiety are two of the most common mental disorders and are characterized by high incidence and high comorbidity. In recent years, the prolonged COVID-19 pandemic and exacerbated social instability have posed significant challenges to the mental resilience and mental health outcomes of the global population. Now more than ever, with an increase in mental health needs, it has become even more crucial to find an effective solution to providing universal mental healthcare.Psychotherapy is of vital importance for those coping with symptoms of depression and anxiety and is used to enhance mental resilience. However, such therapy can be difficult to access in reality.In this context, the Micro-Video Psychological Training Camp (MVPTC) platform will be developed. Objectives: As an online self-help platform for psychological intervention, the MVPTC platform was developed for those who suffer from mild to moderate symptoms of depression and/or anxiety and is tasked with the goal of reducing depressive and anxious symptoms while improving mental resilience. Thus, this study will be carried out to verify its efficacy and applicability. Methods: In this parallel-group, randomized controlled trial, a total of 200 mild to moderately depressed and/or anxious adults seeking self-help will be randomly recruited and assigned to either the Micro-Video Psychological Intervention Group or the Wait List Control Group. Online measurements by self-assessment will be taken at baseline, post-intervention, one-month and three-month follow-up. Results:The primary results will involve symptoms of depression and anxiety. The secondary results will involve mental resilience. An analysis will be conducted based on the intention-to-treat principle. Discussion: This trial will examine whether the MVPTC platform for the relief of symptoms and the enhancement of resilience in a population screened for depression and anxiety symptoms proves effective and applicable. Large-scale resilience enhancement may benefit public mental health in terms of preventive interventions, managing depressive and anxiety symptoms and promoting mental health. With the MVPTC-based method being applied, a brief, efficient, and structured intervention model can potentially be established, having the potential to provide necessary and accessible mental support for an extensive target group.